Kinetic and equilibrium modelling of Cu (II) adsorption from aqueous solution by chemically modified Groundnut husk (Arachis hypogaea). Issue 5 (October 2017) - Gupta, Nitish; Sen, Ravindra
Abstract: Excessive use of heavy metals in industries poses a significant threat to the environment. Enormous amount of copper in water streams due to industrial and agricultural activities causes toxic effects on both flora and fauna. The goal of this study is the removal of Cu (II) from aqueous solutions using abundantly available native groundnut husk (GNH); however owing to low adsorption capacity it is modified by citric acid and termed as citric acid modified groundnut husk (CA-GNH). Batch technique used to study the effects of pH, agitation time, adsorbent dosage, heavy metal ion concentration and temperature on percentage adsorption of Cu (II). Chemical and morphological characteristic of adsorbents were evaluated by Scanning electron microscopy and Fourier transform spectroscopy, respectively. Results showed that CA-GNH showed high percentage adsorption compared to GNH. The equilibrium data were evaluated with the Langmuir, Freundlich and Dubinin–Radushkevich isotherms, and it is found that Langmuir isotherm fitted well. Various kinetic models viz. pseudo first-order, pseudo second-order and intraparticle diffusion were tested and we observe that the pseudo second-order kinetic model could fit. The maximum adsorption capacity calculated by Langmuir isotherm was 33.49 and 15.36 mg/g for CA-GNH and GNH, respectively. Thermodynamic parameters, ΔH, ΔS, ΔG; were computed and it was found that adsorption process was exothermic and thermodynamically favourable. It seems that CA-GNH might be a promising adsorbent for removal of Cu (II) from aqueous solutions.